2018
DOI: 10.1136/jclinpath-2017-204976
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Ki67 analysed by cytology or histology in primary breast cancer

Abstract: AimsThe accuracy of biomarker assessment in breast pathology is vital for therapy decisions. The therapy predictive and prognostic biomarkers oestrogen receptor (ER), progesterone receptor, HER2 and Ki67 may act as surrogates to gene expression profiling of breast cancer. The aims of this study were to investigate the concordance of consecutive biomarker assessment by immunocytochemistry on preoperative fine-needle aspiration cytology versus immunohistochemistry (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
(14 reference statements)
3
17
0
1
Order By: Relevance
“…The proliferation activity of tumours is usually determined with immunohistochemical detection of the cell‐cycle‐specific antigen Ki‐67. Some studies have proved that Ki‐67 expression is a useful prognostic factor in breast cancer . Our results also indicated that Ki‐67 status in post‐operative pathology IHC was the significant prognostic factor, and patients with low SII would have survive longer than those with high SII by Ki‐67 status.…”
Section: Discussionsupporting
confidence: 65%
“…The proliferation activity of tumours is usually determined with immunohistochemical detection of the cell‐cycle‐specific antigen Ki‐67. Some studies have proved that Ki‐67 expression is a useful prognostic factor in breast cancer . Our results also indicated that Ki‐67 status in post‐operative pathology IHC was the significant prognostic factor, and patients with low SII would have survive longer than those with high SII by Ki‐67 status.…”
Section: Discussionsupporting
confidence: 65%
“…In our study, we also examined the Ki-67-score in ER − tumors, and did not observe any substantial differences in this when comparing recurrent cases and controls. Our results are in line with the variability seen in other studies, 45 and underline the complexity and well-known challenges of using the Ki-67 index as a biomarker in clinical decision-making. 46 , 47 …”
Section: Discussionsupporting
confidence: 91%
“…Sampling different tumor regions as with CNBs may therefore affect biomarker agreement as seen in the present study. Low concordance in biomarker status has also been identified between aspiration cytology and histology-based assessments as a sign of sampling error [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%